EFISIENSI PROGRAM PERTUKARAN MAHASISWA MERDEKA II (PMM II) SEBAGAI ALTERNATIF PENGINTEGRASIAN BUDAYA MELALUI KEGIATAN MODUL NUSANTARA (STUDI KASUS PMM II UNIVERSITAS SAMUDRA) - Muhamad Fauzi Efendi; Rima Meilita Sari (Jurnal Samudra Geografi, 2023)
Integrating the nation as a means of strengthening diversity needs to be instilled in students through the Pertukaran Mahasiswa Merdeka (PMM) program. One of PMM activities is the Nusantara Module which functions as social and cultural integration through diversity activities, reflection, inspiration, and social contributions. The purpose of this study was to examine the efficiency of the Nusantara module activities as an alternative to integrating regional culture for the purposes of describing and analyzing results related to the implemented programs. The method used is through a quantitative approach with analytical techniques in the form of descriptive statistics. The instruments used were questionnaires or interviews with a Likert scale system and documentation studies. The number of samples studied were 36 student exchange participants at Samudra University. The results show that the Nusantara module activities are efficient as an alternative to cultural integration.